2011
DOI: 10.1039/c0cc03539d
|View full text |Cite
|
Sign up to set email alerts
|

One-pot synthesis of blue light-emitting Au nanoclusters and formation of photo-patternable composite films

Abstract: Blue light-emitting Au nanoclusters were synthesized in a simple one-pot process via reflux of Au ions with amino-terminated poly(1,2-butadiene) in toluene. DLS results and photoemission spectra showed that Au(8) nanoclusters were successfully formed. Moreover, photo-patterned films containing Au(8) clusters were prepared by photolithography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…For example, several publications have appeared on materials that have been reported to be formed by Au 8 clusters stabilized by macromolecules. [43][44][45][46][47] These materials show fluorescence with blue emission (400-500 nm) and quantum yields of 50 % and above. On the other hand, several gold clusters with molecular structures known from single-crystal analyses exhibit photoluminescence quantum yields of about 1 % or less.…”
Section: Optical Extinction Spectroscopymentioning
confidence: 99%
“…For example, several publications have appeared on materials that have been reported to be formed by Au 8 clusters stabilized by macromolecules. [43][44][45][46][47] These materials show fluorescence with blue emission (400-500 nm) and quantum yields of 50 % and above. On the other hand, several gold clusters with molecular structures known from single-crystal analyses exhibit photoluminescence quantum yields of about 1 % or less.…”
Section: Optical Extinction Spectroscopymentioning
confidence: 99%
“…This suggests the presence of Au 8 clusters according to the spherical Jellium model, 30 which are consistent with those of Au 8 nanoclusters reported in the previous studies. 31 Matrix-assisted laser desorption/ionization-time-of-flight mass spectrometry (MALDI-TOF MS) was performed to confirm the production of Au 8 clusters (see Figure S3 in the Supporting Information). The quantum yield (QY) was 3.1% and 4.2% (calibrated with quinoline as the reference), and the fluorescence lifetime was 2.65 and 5.82 ns for Col-Au NCs and Mac-Au NCs, respectively (see Figure S4 in the Supporting Information).…”
Section: Characterization Of Col-au Ncs and Mac-au Ncs Figures 1a-a mentioning
confidence: 99%
“…Later Liu et al 25 extended this idea of using DMF as both a reducing and stabilizing agent at high temperature and they have succeeded in developing a surfactant-free recipe to synthesize highly stable and luminescent gold nanocluster. Recently, Yabu et al 26 reported a novel one-pot process for the synthesis of AuNC via simple reduction of Au ions by amino-terminated poly(1,2-butadiene) (PB-NH 2 ) in toluene. The synthesized AuNC show PL-emission at 465 nm upon excitation at 370 nm and were characterized as Au 8 clusters (from MALDI-TOF MS analysis).…”
Section: Introductionmentioning
confidence: 99%